Manipulações das variáveis do treinamento de força ou fatores biológicos intrínsecos: o que determina a magnitude da hipertrofia muscular? - Angleri, Vitor (Universidade Federal de São Carlos, 2022)
We aimed to investigate whether muscle fiber cross-sectional area (fCSA) and associated molecular processes could be differently affected at the group and individual level by manipulating resistance training (RT) variables. Twenty resistance-trained subjects had each leg randomly allocated to either a standard RT (RT-CON: without specific variables manipulations) or a variable RT (RT-VAR: manipulation of load, volume, muscle action, and rest interval in a randomly session-by-session fashion). Muscle fCSA, satellite cell (SC) pool, myonuclei content, and gene expression were assessed before and after 16 RT sessions (chronic effect). Additionally, gene expression was assessed 24h after the last training session (an additional 17th session) (acute effect). RT-CON and RT-VAR increased fCSA and myonuclei domain in type I and II fibers after training (P < 0.05). SC and myonuclei content did not change for both conditions (P > 0.05). Pax-7, MyoD, MMP-2 and COL3A1 (chronic) and MGF, Pax-7, and MMP-9 (acute) increased similar for RT-CON and RT-VAR (P < 0.05). The increase in acute MyoG (acute) expression was significantly higher for the RT-VAR than RT-CON (P < 0.05). It was observed correlation between RT-CON and RT-VAR for the fCSA changes (r = 0.89). fCSA changes were correlated with satellite cells (r = 0.42) and myonuclei (r = 0.50) changes. Heatmap analyses showed coupled changes in fCSA, SC, and myonuclei responses at the individual level, regardless of the RT protocol. The high between and low within-subject variability regardless of RT protocol suggests that the intrinsic biological factors seem to be more important to explain the magnitude of fCSA gains in resistance-trained subjects.
Resistance training variables manipulations or intrinsic biological factors: what determines the muscle hypertrophy magnitude?
Keywords: Predisposição biológica; Células satélites; Respostas individuais; Responsividade; Treinamento de força; Variáveis do treinamento; Biological predisposition; Satellite cells; Individual responses; Responsiveness; Resistance exercise; Training variables; CIENCIAS DA SAUDE::EDUCACAO FISICA